Organization of internal communications as a component of strategic communications in the state administration system - Lola, Victoria; Kovalenko, O. (НТУ ДП, 2023)
The impetus for reviewing the role and place of communications was the full-scale invasion of the Russian Federation. In the framework of external communications, the Armed Forces of Ukraine have become an important communication link between the military-political leadership of the state and Ukrainian and international society in the difficult conditions of the unprecedented aggression of the Russian Federation.
Keywords: internal communications